GLOBALISASI EKONOMI, BUDAYA KAPITALIS DAN DEMOKRASI - Dua, Mikhael (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2013)
Globalization, as Anthony Giddens defines it, denotes a shift in the spatial form of human organization and activity to transcontinental or inter-regional patterns of activity, interaction and exercise of power. Under the spirit of capitalism, it can destroy our jobs, hollow out the decision-making power of government, and even threaten the nation-state as the nub of our kind of democracy. Critics of globalization worry about the inability of governments to set their own economic policies. They also worry about the increased power of financial markets to cause economic havoc. Looking at the ethical proposal to this problematic context, this article proposes that we move from an ethical study of the rational foundations of moral norms to a political reflection on the democratic construction of social norms. In such democratic construction, the plurality of views of life will be protected against overweening global capitalism. Kata-kata kunci: Globalisasi, kapitalisme, etika, demokrasi